Analysis of Water Quality and Plankton Biodiversity in Conservation Area of PT PHE Raja Tempira - Boby Muslimin; Khusnul Khotimah; Muhammad Nizar; Helmizuryani Helmizuryani; Henri Yowono; Wahyu Pinto Neri; Indra Sundara Alhusna; Muhamamd Abdul Latif Al-Ansori; Heryadi Heryadi (Universitas Muhammadiyah Palembang, 2024)
Identification of water quality before fish farming is needed to determine the characteristics of water as a medium for freshwater fish cultivation. This study investigated water quality parameters for pH, temperature, Dissolve Oxygen (DO), Total Dissolved Solid (TDS), types and abundance of phytoplankton and zooplankton in the conservation area of PT PHE Raja Tempirai, Penukal Abab Lematang Ilir Regency (PALI), South Sumatra. Water samples were collected from four stations with codes A0, D1 and D2 in the form of earthen ponds and A1, a tributary of the Muara Air Itam river and ex-situ analyzed at laboratory of aquaculture study program, Sriwijaya University and Center for Environmental Health and Disease Control Engineering (BTKLPP) Class I Palembang. All stations have categories very suitable for DO (>6 mg/L) and temperature (29-32 °C) parameters. Station A1 is categorized as less feasible at pH and TDS (5.06±0.72 and 6.80±0.00 mg/L), stations D1 and D2 are suitable for cultivation at pH parameters (6.36±0.11 and 6.71±0.17), and less feasible at TDS (38.63±0.03 mg/L and 34.50±1.90 mg/L). While at station A0 it is very possible on all parameters, but phytoplankton of the genus Peridinium at this station dominate, so in the future, it is necessary to mitigate the abundance of this type of phytoplankton to avoid water quality degradation, especially in different seasons.